Schlieren and PLIF imaging for hydrogen-air detonations - Rojas Chavez, Samir Boset (2019)
Application technologies based on the detonation cycle has proven a significant impact on the overall efficiency. However, detonation engines are not currently available on the markets due to the lack of physical and chemical knowledge of the detonation phenomenon. The present study aims to provide new insights by studying the pressure and velocity, the density gradient of the detonation wave, and the OH distribution on the reaction zone of hydrogen-air detonation. Three strategies were proposed to obtain repeatable detonation events. The strategies vary on the geometry of the obstacle and the amount of spark plug to ignite the mixture. Pressure and velocity were recorded to determine if the transition from deflagration to detonation is successful. To image the density gradient of the shock wave, the optical technique called Schlieren was adapted to the detonation test bench. The OH radical distribution was studied by the optical diagnostic technique called planar laser-induced fluorescence. The pressure trace results showed high peaks in the regimen of Chapman-Jouguet state for detonation, unlike fast flames. The velocity results showed a considerable influence of the obstacle geometry to enhance the velocity of the wave, although the repeatable detonation events and the steadiness of the velocity were not boosted. The third strategy proved that adding more energy to a transient detonation wave, enhanced the stability and the consistent production of detonation events. The Schlieren images revealed the coupling between the reaction and shock wave for detonation, unlike fast flames. Fast flames close to 83% of the Chapman-Jouguet velocity underwent weak decoupling compared to the fast flame with velocities in the range of 40% of the Chapman-Jouguet velocity. The detonation density gradient images, obtained by using a bandpass filter, revealed an irregular cellular structure for different conditions when detonation occurs. The single image obtained by the technique planar laser-induced fluorescence at 0.5 bar, 293 K, and stoichiometric mixture showed the influence of the cellular structure of the shock wave into the reaction zone since an irregular cellular structure was captured at the beginning of the reaction zone. The fluorescence intensity profile registered the maximum values at the beginning of the reaction zone, followed by a fast decrease of the intensity.